2018
DOI: 10.31557/apjcp.2018.19.12.3415
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms (SNPs) in Genes Encoding for Folate Metabolising Enzymes with Glioma and Meningioma in Indian Population

Abstract: Background: The association of primary brain tumors with Single Nucleotide polymorphisms (SNPs) in genes of folate metabolising enzymes have been reported to vary among different ethnic population. Here, we have studied the association of SNPs of folate metabolizing genes with the primary brain tumors (glioma and meningioma) in North Indian population. Methods: SNPs of genes coding for folate metabolizing enzymes was carried out in 288 study population from North India … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
8
0
1
Order By: Relevance
“…Therefore, folate and vitamin B6 and B12 levels should be included in MTHFR polymorphism studies in cancer risk assessment. One literature report observed no significant difference in the serum folic acid and vitamin B12 levels concerning MTHFR polymorphisms [ 107 ]. Additionally, they found no association between meningioma or glioma risk and the MTHFR C677T polymorphism in the Indian population.…”
Section: Mthfr C677t and A1298c Polymorphisms And Gliomamentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, folate and vitamin B6 and B12 levels should be included in MTHFR polymorphism studies in cancer risk assessment. One literature report observed no significant difference in the serum folic acid and vitamin B12 levels concerning MTHFR polymorphisms [ 107 ]. Additionally, they found no association between meningioma or glioma risk and the MTHFR C677T polymorphism in the Indian population.…”
Section: Mthfr C677t and A1298c Polymorphisms And Gliomamentioning
confidence: 99%
“…Several studies have found no association between polymorphisms and glioma development [ 100 , 107 , 111 ] and overall survival [ 112 ]. Notably, the influence of ethnicity in MTHFR polymorphisms is associated with glioma risk.…”
Section: Mthfr C677t and A1298c Polymorphisms And Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…Glioblastoma (GBM) represents the most common primary brain tumor in humans with an average incidence rate of 3.21 per 1,00,000 population [1]. Recent studies have reported the incidence of glioma in India is 1-4 per 1,00,000 [2][3][4]. The prognosis of GBM remains poor despite developments in neurosurgery and chemoradiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that single-nucleotide polymorphisms (SNPs) were the most frequent single-nucleotide variations that occur in a specific position. Numerous SNPs, such as those in XRCC1/4, ERCC1/4, MGMT, PARP1, and MTHFR have been demonstrated to contribute to glioma susceptibility 1,7…”
Section: Introductionmentioning
confidence: 99%